Analisis Kesetaraan Gender di dalam Dunia Pendidikan dan Dunia Kerja dengan Mempertimbangkan Kepercayaan Norma Budaya Matrilineal dalam Budaya Minangkabau - Yefiza Nahri Agustia; Slamet Tri Wahyudi (AHKAM, 2025)
Gender inequality is a structural issue deeply rooted in many countries, including Indonesia, and is manifested in domestic, political, educational, and occupational domains, even though the right to gender equality is inherently held by all individuals without exception. Patriarchal culture in Indonesia remains a firmly entrenched reality that positions one group as the primary holder of authority and control in various spheres of life, thereby generating injustice and gender disparities that disadvantage women and hinder national progress. This article aims to analyze the influence of matrilineal culture in Minangkabau society on women’s representation in education and the world of work, to identify matrilineal cultural factors that shape this representation, and to formulate strategies within a matrilineal cultural framework to enhance women’s involvement in bela negara. The discussion focuses on how the values and social structures of Minangkabau matrilineal culture can serve as a counterbalance to the dominance of patriarchal systems while simultaneously opening broader spaces for women’s participation in the public sphere. Through this analysis, the article argues that a deeper understanding of Minangkabau matrilineal culture has the potential to provide a conceptual foundation for strengthening women’s representation in the education sector and the labour market, as well as for designing more contextually grounded strategies to promote women’s active role in bela negara.